Technical and Financial Assessment of Photovoltaic Solar Systems for Residential Complexes Considering Three Different Commercial Technologies and Colombia’s Energy Policy - Muñoz, Yecid; Carvajal, Luz Helena; Méndez, Juan Pablo; Niño, Javier Camilo; De la Rosa, Miguel Angel; Ospino, Adalberto (International Journal of Energy Economics and Policy, 2021)
The use of solar energy is increasingly prevalent in residential areas around the world due to the decrease in the levelized cost of energy (LCOE) for projects that meet the energy need in homes, in Colombia regulations have begun to facilitate the integration of grid-connected renewable energy projects and in isolated areas. The purpose of this research is to technically and financially assess the feasibility of a solar photovoltaic system connected to the grid in a residential complex in Colombia according to the regulatory framework in force at 2020, comparing three photovoltaic module technologies, as well as three generation scenarios (self-consumption, exchange with the network and sale of surpluses), financial feasibility was assessed taking into account three financial goodness criteria (NPV, IRR and Payback Time). The results of the research indicate that the most feasible generation scenario technically and economically is self-consumption using Si-Poly technology, for the self-consumption scenario the solar photovoltaic system requires an installed capacity of 3.77 kW peak, with an investment cost of 5,748 USD, according to the criteria of kindness the Payback Time is 7 years, with an IRR of 19.67% for the project and 49,920 USD of NPV. Keywords: PV System ON Grid, solar communities, Colombian renewable energy regulations, technical and economic analysis. JEL Classifications: Q2, Q4, Q55 DOI: https://doi.org/10.32479/ijeep.9981